Guazuma Ulmifolia: A Review on its Traditional Uses, Phytochemistry and Pharmacology - Dr. Neha Shekhawat (International Journal of Pharma and Bio Sciences, 2021)
Guazuma ulmifolia Lam. belongs to the family Sterculiaceae and is commonly called Bastard cedar or Mutamba. It is one of the most useful traditional medicinal plant in India. During the last five decades, considerable progress has been achieved regarding the biological activity and medicinal applications of Mutamba. The extracts and metabolites of Guazuma ulmifolia particularly those from leaves and bark possess several useful therapeutic activities and recently, these compounds were reported to possess various biological activities including antibacterial, antiviral, antifungal, anti-inflammatory, antisecretory, antitumor, antioxidant and cytotoxicity. Phytochemically this plant contains fatty acids, steroids, flavonoids, tannins, glycosides, carbohydrates and mucilage. The traditional uses of G. ulmifolia have been experimentally proved by in vitro and in vivo studies, in which its bioactivities were associated with its phytochemical composition, mainly proanthocyanidins. It is now considered as a valuable source of unique natural products for development of medicines against various diseases and also for the development of industrial products. Its leaves and roots are used in home remedies against dysentery and diarrhea, in the treatment of prostate, as a uterine stimulant and other diseases. Due to the characteristics presented and the growing interest in this species, a systematic review was carried out on the possible pharmacological and toxicological effects of Guazuma ulmifolia Lamark. This review gives a bird’s eye view mainly on the biological activities of some of the bioactive compounds of Mutamba, pharmacological actions of the mutamba extracts, clinical studies and plausible medicinal applications of mutamba along with their safety evaluation.